Growth and Microhardness Studies on Bismuth Sulpho Fluoride Single Crystals - Kumararaman, S.; Sundaresan, N. (Asian Journal of Chemistry, 2010)
Bismuth sulpho flouride is one of the ternary compounds belonging to V-VI-VII group compounds. Being a ferro electric crystal, it exhibits various interesting properties. Thiourea solution of concentration 10% by weight was prepared. It was mixed with bismuth oxide in hydrogen flouride and crystals were harvested. For the indentation test Vicker's hardness tester was used. The mechanical properties were discussed.